Microflora of Ciku (Achras sapota L.) of Variety Jantung - Abu Bakar, F.; Abdul karim, Mohd Nordin (1990)
The overall microbial count of ciku is law and predominantly )'east. which peaks at day three after haverst. Washing reduced the microbial counts of the fruits, retarding the yeast population by 89% and bacteria by 75 %. During injury, the dominant flora is bacteria which is replaced later by fungi as the storage time progeressed. Normal microbial flora of aim consists of bacteria, yeasl and moulds. Spoilage during cold storage is associated with new strains of,yeast and moulds. Proper sanitation and post harvest handling treatments are important in controlling fruit losses associated with microorganisms.